DINAMIKA FEAR OF MISSING OUT (FOMO) PADA INTERAKSI SOSIAL I-GENERATION DALAM ADIKSI BERMEDIA SOSIAL DI JORONG SAWAH PARIK KECAMATAN TANJUNG BARU KABUPATEN TANAH DATAR - Delia Faramita; Siti Fadila (KINEMA: Jurnal Komunikasi dan Penyiaran, 2023)
Abstract: This research examines the phenomenon of fear of missing out (fomo) in i-generation social interactions in social media addiction in Jorong Sawah Parik. The trigger is because of the intense interest between the i-generation and social media. The aim of this research is to describe the dynamics of FoMo, and the impact of FoMo on i-generation social interactions in social media addiction. This research uses field research with a qualitative descriptive approach. The data collection techniques used are through observation, interviews and documentation. Data analysis uses the Miles & Huberman analysis model, namely by collecting data, reducing data, presenting data, and concluding with effective sentences. From the field research conducted, it was found that the FoMo dynamics of the i-generation's addiction to social media in Jorong Sawah Parik occurred due to several things, namely: from the use of social media, cellular accessibility, and the intensity of social media use which caused the i-generation to experience feelings of left behind both information and other new things. Meanwhile, the impact of FoMo on i-generation varies for each informant. Judging from its positive impact, FoMo provides motivation to try new productive things, increases productivity, and makes it easier to communicate and obtain information. If viewed from the negative impact, FoMo can cause social pressure, dependence and addiction, neglect of time, decreased self-confidence, and decreased quality of direct interactions.┬áKeywords: Fear of Missing out (FoMo), I-generation, Social Media┬á